Penerapan Metodologi Agile dalam Pengembangan Perangkat Lunak - Chandra Ramadhan; Mamok Andri Senubekti; Dien Amalia (Router : Jurnal Teknik Informatika dan Terapan, 2025)
This literature review discusses the application of Agile methodology in modern software development. Agile offers a flexible, iterative approach that contrasts with traditional waterfall models. The objective of this study is to provide insights into how Agile frameworks such as Scrum, Kanban, and Extreme Programming have influenced development speed, software quality, and team collaboration. Methodologically, the study synthesizes findings from recent academic and industrial literature from the last five years. The results show that Agile enhances adaptability and customer satisfaction, although challenges remain in large-scale implementations.